Enhancing resistance training adherence in older adults with sarcopenia or osteoporosis: a study on referral success rates - Lin, Ching-Huang; Cheng, Yun-Ju; Hsu, Ching-Ping; Hu, Gwo-Chi; Hsu, Hsin-Yin; Chien, Yu-Ning; Lin, Hsin-Hui; Hwang, Lee-Ching; Ma, Hsiao-Chi; Lin, Fang-An; Tsou, Meng-Ting; Wu, Tung-Ke (Frontiers in Public Health, 2025)
BackgroundSarcopenia and osteoporosis increase the likelihood of disability and caregiving burden. While progressive resistance training (PRT) is effective in mitigating these outcomes, patients often struggle to find suitable, long-term training facilities, making it difficult to adhere to exercise prescriptions.ObjectivesThis feasibility study aimed to familiarize patients with PRT through educational training by a geriatrician, enabling them to identify a suitable long-term community-based training program.Participants and methodsForty-one patients diagnosed with osteoporosis or sarcopenia at a medical center in Taiwan were enrolled via the researchers’ LINE app platform. Finally, 11 participants with osteoporosis were recruited. Among them, four had vertebral compression fractures and two also met the diagnostic criteria for sarcopenia. The median age was 68 (range 63–69) years, DXA femoral neck T-score was −3.3 (−3.5–−2.2), and grip strength was 22.4 (20.3–26.7) kg. After cardiopulmonary exercise testing (CPET), participants received up to 10 PRT sessions, with vital signs monitored. In each session, researchers focused on six key learning points of free-weight PRT, addressed difficulties hindering progress, encouraged participants to find community-based training courses, and provided training summaries to external trainers. Descriptive statistics summarized patient data and referral rates. The primary outcome was the success of referrals to community-based training. Secondary outcomes, to be reported later, included changes in grip strength, DXA bone mineral density, DXA muscle mass, CPET results after 6 months, and sustainability of long-term resistance training (RT) in older people with osteoporosis or sarcopenia.ResultsThe recruitment success rate was 26.8%. Baseline characteristics did not correlate to successful referrals. A total of 67 physician-guided PRT sessions were conducted for the 11 participants. On average, after 4.5 in-hospital sessions, five participants secured self-paid one-on-one RT in the community, and one joined group training, resulting in a referral success rate of 54.5%.ConclusionThis feasibility study aimed at achieving successful referral for long-term community-based RT. It provides valuable insights for future research on RT for patients with osteoporosis or sarcopenia, making exercise a sustainable and quantifiable intervention.